Ethiopian Adoptees' Experiences of Attachment after Adoption in Australia: A Qualitative Study. Issue 3 (3rd July 2022) - Winkenweder, Hilina; Due, Clemence; Strelan, Peter
Abstract: This study investigates how Ethiopian adoptees and adoptive parents in Australia experience attachment to each other post-adoption. Semi-structured interviews were conducted with eight Ethiopian adoptees and eight adoptive parents. Thematic analysis returned four themes, indicating that attachment experiences were affected by the following: age at adoption; separation anxiety and survival mechanisms; biological family access; and identity formation. The findings contribute to improved understanding of Ethiopian adoptees' attachment experiences in Australia, and highlight unmet needs surrounding post-adoption support, in particular, support relating to post-adoption attachment.